The Interplay between Freedom and Confinement in No Exit by Taimur Kayani - Hameed, Farrukh; Latif, Zainab (JELLL, 2023)
The present study explores the interplay between freedom and confinement in the play No Exit by Dr. Taimur Kayani. The researchers have analyzed the character of Mujtaba from the perspective of Jean-Paul Sartre’s philosophy of being-in-itself to being-for-itself, which Sartre describes in his book Being and Nothingness. Moreover, this study aims to consider the ideas of freedom vs. confinement, how Mujtaba’s erratic actions are harming his freedom, and how Mujtaba’s thinking is constrained by his culture, traditions, religion, and memories from his past. The researchers have utilized qualitative type of research and analyzed it descriptively. It shows that Mujtaba’s absurd thoughts and inner desires transform when he accepts the concept of ‘being for itself’ by Sartre. Kayani’s play bears the touches of Sartre’s theory of existentialism. It symbolizes that many Mujtabas in society have fallen into this situation in distant lands. It discusses various issues like injustice, family crises, and financial issues. The objective of the study is to explore the hard and grim conditions of illegal immigrants who remain empty-handed at the end of their journey, but still, they can get freedom by opting for the right choices. Furthermore, it concludes that Kayani wants his audience to get freedom before it is too late to lose their existence.